2014
DOI: 10.1038/cddis.2014.127
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of low DICER expression regulated by miR-130a in cervical cancer

Abstract: Dicer is crucial for the maturation of microRNAs (miRNAs) and its dysregulation may contribute to tumor initiation and progression. The study explored the clinical implications of Dicer and its post-transcriptional regulation by microRNAs in cervical cancer. qRT-PCR and immunohistochemistry investigated Dicer mRNA and protein levels in cervical cancer tissues. The relationship between Dicer expression and survival was analyzed. MiRNA target prediction identified miRNAs that might target Dicer. Luciferase repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 37 publications
(41 reference statements)
1
51
1
2
Order By: Relevance
“…DICER possesses a complex role in cancer through its ability to regulate the maturation of miRNA (Lyle et al, 2014). Growing research suggests that dysregulated expression of DICER might play a vital role in cancer risk and prognosis (Caffrey et al, 2013;Avery-Kiejda et al, 2014;He et al, 2014). Given the critical function of DICER in miRNA processing and the involvement of miRNAs in cancer development and progression, it is rational to speculate that host genomic polymorphism of DICER may influence the cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…DICER possesses a complex role in cancer through its ability to regulate the maturation of miRNA (Lyle et al, 2014). Growing research suggests that dysregulated expression of DICER might play a vital role in cancer risk and prognosis (Caffrey et al, 2013;Avery-Kiejda et al, 2014;He et al, 2014). Given the critical function of DICER in miRNA processing and the involvement of miRNAs in cancer development and progression, it is rational to speculate that host genomic polymorphism of DICER may influence the cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…miR-130a has been observed to play a critical role in various types of cancer. He et al (35) observed that miRNA-130a was upregulated in cervical cancer, which directly targeted Dicer mRNA, enhancing cellular growth, migration and invasion. In contrast, Li et al (36) detected that miR-130a was significantly downregulated in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-130a, miR-19, and miR-101 coregulat ATXN1 (ataxin 1) expression to modulate Spinocerebellar ataxia type 1 pathogenesis [68]. Additional studies revealed that miR-130a targets DICER1 (dicer 1, ribonuclease type III) in chronic lymphocytic leukemia [69] and cervical cancer [58]. In summary, miR-130a targets different genes associated with different diseases, emphasizing that the miRNA can bind to a number of diverse mRNAs.…”
Section: Discussionmentioning
confidence: 97%
“…Studies indicate that miR-130a is associated with lung cancer [50], gastric cancer [51,52], ovarian cancer [53][54][55][56][57], cervical cancer [58,59], and prostate cancer [60]. Recently, deep sequencing technology was used to identify differentially expressed host miRNAs in chickens [28,34,35,61,62].…”
Section: Discussionmentioning
confidence: 99%